Last Chance to See? Motivations and Outcomes of Last Chance Tourism Experiences in Arctic Alaska - Wilson, Tana Kay (Clemson University Libraries, 2019)
The tourism market for endangered places and their vulnerable resources are booming and widely referred to as last chance tourism (LCT). People are planning trips to experience places or see species they may never have wanted to see until learning that the option to witness it could disappear in their lifetime. The notion of LCT was first introduced by the tourism industry to describe increasing tourist interest to endangered destinations. Utilizing visitor surveys, the purpose of this study was to identify LCT participants and quantify experiential outcomes of LCT (e.g., awe, epiphany and ambassadorship). This study specifically takes place at Kaktovik, Alaska, USA near the Arctic National Wildlife Refuge. There are three dimensions of last chance tourism around Kaktovik that make this location unique and exemplar for a LCT study: (1) shifting Arctic landscapes, (2) the dynamic Iñupiat culture of Kaktovik, and (3) a threatened Southern Beaufort Sea population of polar bears.